Impact of obesity on vitamin D and calcium status - Shah, Pankil; P Chauhan, Asutosh (International Journal of Medical Research and Review, 2016)
Introduction: Obesity is associated with metabolic syndrome. Obesity is a leading preventable cause of death worldwide, with increasing rates in adults and children. Obesity is associated with vitamin D insufficiency and hyperparathyroidism, secondary hypercalcemia. The purpose of this study is to test effect of obesity on Vitamin D and calcium level. Methods: The present study investigated effect of obesity on Vitamin D and calcium level. We studied 150 Subjects with no pre-existing disease and not taking any nutritional suppliments for vitamin D. At a baseline they were asked about their family history of obesity. Subjects are investigated for 25-hydroxyvitamin D [25(OH) D] and serum Total calcium level to study effect of obesity on vitamin D and calcium status. Results: Out of 150 subjects included in the study, 107 had obesity and 43 subjects was non-obese. The Body Mass Index less than 30 is taken as cut off point for defining obesity. The mean value of 25-hydroxyvitamin D was 13ng/ml in the group of obese people and the same was 28ng/ml in the group of non-obese individuals. This change was statistically significant (p<0.05). The mean value of serum Total calcium level was 13mg/dl in the group of obese people and the same was 10mg/dl in the group of non-obese individuals. This change was statistically significant (p<0.05). Conclusions: It is concluded that obese individuals are increased risk of developing Vitamin D Deficiency and secondary hypercalcemia.